2011
DOI: 10.1016/j.jbi.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Deviations from protocol in a complex Trauma environment: Errors or innovations?

Abstract: Protocol standardizations are important for consistent and safe practices. However, complex clinical environments are highly dynamic in nature and often require clinicians, confronted with non-standard situations, to adjust and deviate from standard protocol. Some of these deviations are errors which can result in harmful outcomes. On the other hand, some of the deviations can be innovations, which are dynamic adjustments to the protocols made by people to adapt the current operational conditions and achieve h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…Definitions of violations offered in two of the seven studies specified that violations were not intended to harm [40,43]. In other studies, definitions offered for first order problem solving and deviations matched our definition of workarounds [24,58,59,73]. In this paper we use the term workaround to refer to behaviours that match the definition in this study (e.g.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Definitions of violations offered in two of the seven studies specified that violations were not intended to harm [40,43]. In other studies, definitions offered for first order problem solving and deviations matched our definition of workarounds [24,58,59,73]. In this paper we use the term workaround to refer to behaviours that match the definition in this study (e.g.…”
Section: Resultsmentioning
confidence: 98%
“…Study settings comprised hospitals that provided general medical, specialised paediatric and psychiatric services [60], and a variety of wards including, but not limited to: intensive care [1,4,35,58,59,61-66], medical and surgical [1,4,35,45,46,58,59,62],[64,66-70], oncology [1,50,58,59,62,64,65], maternity [1,58,59,62,66,67,71], cardiac units [1,45,50,58,59], operating theatre units [38,52,62,72], emergency and trauma departments [35,57,58,62,73-75], outpatient clinics [76] and paediatrics [1,35,40,53,54,58-60,63-66,71]. These wards were identified in academic [48,49,58,64,71,75,77,78] and non-academic [58,61,72], community [1,58,59,61,62,72,79], tertiary [45,58,64] and teaching hospitals [1,40,46,52-54,59,79], in urban [1,45,53,...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that trauma physicians (experts), when they deviated from standardised protocols, made significantly fewer errors when compared with first-year and second-year residents (comparative novices) 44. The deviations occurred under conditions of complexity, as well as in the presence of high levels of uncertainty about the patient's condition.…”
Section: Error Generation and Recoverymentioning
confidence: 85%
“…Over the past decade, Patel and colleagues have carefully documented the reasons medical errors occur, with special appreciation for the role of complexity in clinical situations 2 3. Due to that complexity, and in recognition of the fallibility of human care, the issue quickly becomes how to mitigate errors before patients are adversely affected.…”
mentioning
confidence: 99%